2018
DOI: 10.1556/2006.7.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder and addictions (substance and behavioral): Prevalence and characteristics in a multicenter study in France

Abstract: It seems essential to determine students' problems and propose interventions adapted to students' needs, in order to reduce the negative impact on their future academic and global successes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
1
21
0
4
Order By: Relevance
“…Alcohol use disorder in people with ADHD is prevalent, ranging from 19% to 26% of young adults in different countries. 23,24 The prevalence of ADHD in people with alcohol use disorder has a similar range in adolescents, 25 and rises to 33% in adults. 25,26 Early-onset ADHD has been prospectively associated with future alcohol use and alcohol use disorder.…”
Section: Attention-deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…Alcohol use disorder in people with ADHD is prevalent, ranging from 19% to 26% of young adults in different countries. 23,24 The prevalence of ADHD in people with alcohol use disorder has a similar range in adolescents, 25 and rises to 33% in adults. 25,26 Early-onset ADHD has been prospectively associated with future alcohol use and alcohol use disorder.…”
Section: Attention-deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…College practitioners and psychologists could assess for a learning disorder or attention deficit disorder to offer evidence-based medicine treatment. This would potentially reduce binge alcohol drinking and illicit substance use [39].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists various studies indicating an interdependence between the risk of alcohol use and ADHD patients [4,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Several studies have reported that ADHD and alcohol abuse have a direct positive correlation [30][31][32][33][34][35][36][37][38][39][40][41]. Nevertheless, there have been many contradictory reports showing that the risk of alcohol abuse does not depend on ADHD [4,[42][43][44].…”
Section: Reviewmentioning
confidence: 99%